What barriers impede the access to healthcare toward Lesbian and Gay men: a cross-sectional study of liver transplant surgeons in China - Yi Xu; Ziyang Zeng; Lijuan Zhang; Minghong Sun; Yi Tao (Annals of Medicine)
Background Sexual minorities face healthcare prejudice, with clinicians often lacking knowledge of their specific needs.Objective Investigate factors influencing Chinese liver transplant surgeons’ attitudes toward lesbians and gay men to advance health equity.Methods .A cross-sectional web-based survey was performed in China Liver Transplantation Congress. The questionnaire included their socioeconomic characteristics, willing to receive patients with same sex orientation, the perception of lesbian and gay men, HIV cognition, previous lesbian and gay men admission history and the attitudes toward lesbians and gay men (ATLG). The structural equation model (SEM) was constructed to analyze the relationship of influencing factors of liver transplant surgeons’ attitudes toward lesbian and gay men.Results  Among 142 Chinese liver transplant surgeons, attitudes toward lesbians and gay men significantly differed by age, marital status, education, position, treatment willingness, HIV knowledge, and prior clinical exposure. Structural equation modeling demonstrated: (1) Positive HIV knowledge–treatment history association (β = 0.32, p < 0.05); (2) Socioeconomic status (β = 0.241, p = 0.01) and unawareness of MSM HIV susceptibility (β = 0.176, p = 0.04) reduced ATLG scores; (3) Prior clinical exposure predicted positive attitudes (β = −0.276, p = 0.02); (4) Lower treatment willingness associated with negative ATLG (β = −0.317, p = 0.003).Conclusion This study elucidates the factors that influence and mediate liver transplant surgeons’ attitudes towards lesbian and gay men, as well as their willingness to treat them, with the aim of enhancing health equity for this marginalized group.